Enhanced Sensitivity Temperature Sensing Based On Second Order Brillouin Slow Light - Pang, Wen Shean (2021)
In the past few decades, fiber optic sensors emerged as a technology that had shown superior sensitivity, range, resolution and measurement speed. The incorporation of fiber optic sensors into communication systems enabled sensing in harsh environments. This is to resolve the issues with sparks, electromagnetic interference and long distance transmission, which is unachievable using electronic sensors. In the recent few decades, there is an abundance of existing and ongoing researches on discrete optical sensing (FBG, interferometer and photonic crystal fiber) and distributed optical sensing (BOTDA, BOCDA, BOFDA and BOTDR). Distributed sensing is mainly based on the nonlinear stimulated Brillouin scattering (SBS) process. Alternatively, SBS can be used to produce slow light, which is used in slow light sensing. SBS slow light sensing should be explored because the cost, complexity of configuration and difficulty in data acquisition are potentially reduced compared to contemporary distributed sensing systems. Most of the distributed sensing systems required sophisticated signal processing in order to acquire the sensing parameters. ii This dissertation shows the experimental studies on the characterization of SBS in optical fiber, with continuation of work in Brillouin slow light generation and characterization. Next, Brillouin slow light is used to perform temperature sensing. The configuration comprises of a seed signal generator and sensing region. Further improvement of the sensitivity is done by exploring higher order SBS slow light in the sensing system. In SBS characterization, 2km, 5km and 10km fiber spools are used. For the first order setup, the BS1 threshold power are 101mW, 61mW and 26mW for lengths of 2km, 5km and 10km respectively. As for the second order setup, the BS2 threshold power are 124mW, 89mW and 53mW. Then, the relative Brillouin gains of first and second order setups are compared with the initial pump power of 13.19dBm. The delay increments with increasing Brillouin gain are 1.2ns/dB for first order and 6.67ns/dB for the second order setup. Finally, the first and second order SBS slow light temperature sensing systems are investigated and compared to show the sensitivity improvement. For the first order system, the sensitivity is 1.111ns/°C. Then, it is showed that the sensitivity almost doubled to a value of 1.918ns/°C for the second order system. This increase in sensitivity should prompt for a deeper research in higher order SBS sensing. With the enhanced sensitivity of fiber sensor system, it will definitely be potentially to be applied in sectors operating in harsh environment which need crucial monitoring.